Interferons as a Potential Therapeutic Drug for COVID-19: A Literature Review of Mechanisms, Current Clinical Trials, and Challenges - Yadav, Pramod; Chandra, Vishal; Raghuvanshi, Vikas; Yadav, Amarjeet; Yadav, Adhishree; Ali, Samim; Mani Tripathi, Vivek (Journal of Community Medicine and Health Solutions, 2023)
The 2019 COVID-19 pandemic caused by SARS-CoV-2 has resulted in many fatalities worldwide. Despite various types of supportive care, mortality rates for patients with comorbidities remain high. To explore alternative treatment options, interferons (IFNs) have emerged as promising therapeutic drugs for SARS-CoV-2. This review aims to investigate the potential of IFNs as a drug with details on their mechanisms of action, and available data on their use with ongoing clinical trials, results, potential limitations, and challenges. Recently published research articles, which are systematically searched through online databases, have been selected and found that IFNs have colossal potential in treating SARS-CoV-2 infection by modulating the host’s immune response and inhibiting viral replication and decreasing the severity of disease and hospitalization (p = 0.03, ± 0.05) and (p = 0.04, ± 0.05) respectively. However, due to less available data, more controlled and randomized trials are needed to confirm the efficacy and safety of IFN therapy. The optimal dosing and duration of IFN therapy also remain to be determined. Although further research is needed the wait for ongoing clinical trial results under investigation is also important for a better understanding of IFN therapy.